Cream Formulation Of Extract Of Maja Leaves (Crescentia cujete) As An Antimicrobial Against Staphylococcus aureus - Siti Nurjanah; Yuli Wahyu Tri Mulyani; Laila Susanti; Samsuar Samsuar; Mashuri Yusuf; Meidaliyantisyah Meidaliyantisyah (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2021)
Maja (Crescentia cujete L) is a plant that has medicinal properties for various diseases. Leaves of Maja contain some compounds such which are thought to have the potential to be antibacterial. The purpose of this study was to determine the potential of maja leaf extract in cream dosage form and to prove the presence of Antibacterial activity against Staphylococcus aureus. The cream of Maja leaf extract was made into several formulations; (5, 10, 15 %) The results was the cream of Maja leaf extract was able to inhibit the growth of S. aureus with the largest inhibition zone at a concentration of 15% with an average of 11.52 ± 0.95mm. Cream formulations were evaluated physically; organoleptic was resulting F1 in brownish-green, F2 in brown, and F3 in dark brown. Homogeneity tests show that all formulations were homogeneous. The pH value of all formulations following the cosmetic standard was about 4.5 – 6.5. The standard viscosity value was between 2000 – 4000 cps. The stability test of cream preparations shows no changes in the form of low-temperature storage (4ºC), room temperature, and high temperature (40ºC), so that maja leaf extracts can be formulated in cream preparations and cream formulations